MENJAGA HAFALAN QUR’AN DI TENGAH ARUS MODERNISASI: STUDI TENTANG STRATEGI DAN TANTANGAN GURU TAHFIDZ - Mhd Hazrat Khairi; Mahariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the strategies and challenges of Tahfidz teachers in maintaining students' memorization. The focus of the study in this research is three things, namely the teaching strategies used by Tahfidz teachers, the challenges faced by Tahfidz teachers, and the evaluation methods used by Tahfidz teachers to measure the success of students' memorization of the Qur'an. The research method used in this study is qualitative based on a phenomenological approach with data collection techniques through observation, interviews, and documentation. The collected data were then analyzed using the Miles and Huberman technique, namely data reduction, data presentation, and conclusion drawing. The research findings explain that the learning strategy used by Tahfidz teachers in maintaining students' memorization is muraja'ah and testing the memorization of each student once a month. The challenge faced by Tahfidz teachers is that many students are not optimal in memorizing the surah targeted by Tahfidz teachers. The evaluation method used is testing the students' memorization once a month, and holding a competition between students once a year.